Perspectives of post-commencement financiers regarding their voting rights on a business rescue plan - Van Niekerk, Larisa (University of Pretoria, 2024)
Post-commencement financiers provide a lifeline to companies under business rescue and these financiers have their best interest in the survival of these companies. Should it be that the business rescue plan is unsuccessful, the chances are that the post commencement financiers will be the largest creditors. In Wescoal Mining (Pty) Ltd v Mkhombo NO, a dispute arose regarding the appropriate adoption of a business rescue plan during the meeting. One critical legal issue was whether the Companies Act bestows voting rights exclusively to the company's creditors who existed at the initiation of business rescue, or if creditors accruing after the commencement may also partake in voting on the plan. Following an assessment by Judge Wilson, it was established that only creditors with claims predating the commencement were eligible to participate in the voting process. Subsequently, Judge Wilson believed that section 135 of the Companies Act places post-commencement financiers as creditors in a different class and provides for their protection and interests in a different way. Against this background, the dissertation evaluates the position of post-commencement creditors when it comes to voting on a business rescue plan.
Keywords: Business rescue; Company law; Creditors; Insolvency; Insolvency law; Life-line; Post-commencement creditors; Post-commencement finance

The relationship between the business rescue practitioner and the directors of the company - Mokoka, Neo (University of Pretoria, 2024)
This dissertation on the relationship between the business rescue practitioner and the directors of the company under business rescue. In essence, this dissertation investigates whether a conflict arises between the duties, roles and powers of the business rescue practitioner and those of directors of the financially distressed company. The aim of this dissertation is to study what are the limitation on duties, roles and powers of directors of the company as a result of the appointment of the business rescue practitioner and the extent thereof. In achieving the above objective, this dissertation commences with setting out the background of business rescue proceedings in South Africa by analysing provisions of Chapter 6 of the Companies Act 71 of 2008 which has introduced “a new corporate rescue procedure” in South Africa, being business rescue. The focus is on provisions dealing with duties, roles and powers of directors in the ordinary course as set out in section 66, 75 to 77 of the Act. The focus then shifts to the provisions dealing with the commencement of business rescue proceedings, the appointment of the business rescue practitioner and his duties, roles and powers. In order to establish whether a conflict truly exists between the duties, roles and powers, various sources dealing with this issue are considered. In order to assess whether there are solutions in dealing with the conflict and/or limitation that arises, this dissertation includes a comparative study on selected foreign jurisdictions dealing with the interaction between the board of directors and business rescue practitioner are considered. In particular, this dissertation considers corporate rescue mechanisms in the Commonwealth of Australia, the United Kingdom and the United States of America. The purpose of the comparative study is to determine which lessons can be learned from the practices in the aforementioned jurisdictions. The overall objective of this study is to determine how the South African legal framework pertaining to the interaction between directors and business rescue practitioners can be enhanced.
Keywords: Business rescue; Business rescue practitioner; Companies Act 71 of 2008; Comparative study; Duties of directors; Limitations on powers; Powers of directors; Roles of directors; US bankruptcy code

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

L'arbitrage à l’épreuve des procédures collectives et de l’intervention du juge en droit de I’OHADA. - Kante, Souleymane (Université Jean Lorougnon Guédé, 2021)
Si l’on définit l’arbitrage simplement comme un mode de règlement des différends administré par les particuliers non investis de leur mission par l’Etat. Il n’en demeure pas moins que ce mode de règlement des différends ne saurait évoluer seul. C’est ainsi que l’ordre public des procédures collectives et l’intervention du juge étatique impact tant l’arbitrage. Il a paru important de jauger leur impact sur l’arbitrage. L’analyse effectuée à travers une méthode exégétique des textes communautaires et internationaux a permis de constater que les procédures collectives et l’intervention du juge étatique sont facteurs de désordre dans l’arbitrage. Toutefois, il convient de relever une certaine survie de l’arbitrage face aux procédures collectives et à l’intervention du juge étatique.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Juge étatique; OHADA; Procédures collectives; Survie

La responsabilidad penal en el concurso de acreedores: los delitos de insolvencia punibles - Campos Rodríguez, Manuel (Universidad de Sevilla, 2021)

The release of liability of a surety during business rescue proceedings - Dubula, Mcebisi (University of KwaZulu-Natal, 2019)
Chapter 6 of the companies Act has attempted to resolve problems created by the ineffectiveness of judicial management which has failed to provide suitable alternative to the liquidation. The process of business rescue proceedings has made some impact on the liability of sureties in so far as it relates to creditors. Moratorium has been imposed once the business rescue proceedings commences and therefore the principal debtors are protected against any legal action unless the court or business rescue practitioner has consented thereto. The question is what is the impact of the business rescue proceedings on the rights of creditors against the sureties of the company under business rescue proceedings and what is the judicial position in so far as it relates to liabilities of sureties during business rescue proceedings, finally what is the position of comparative law in respect of other foreign Jurisprudence terms of business rescue proceedings and the liability of sureties. The South African Companies Act does not regulate the situation of creditor’s rights against sureties of a financially distressed Company. In terms of American law, the situation is different. Creditor’s rights against non-debtors (including sureties) is regulated by Bankruptcy Codes. In terms of bankruptcy codes, the discharge of a debtor does not affect the liability of the nondebtors or other entities. There are divergent views in terms of South African Court decisions in respect of liability of sureties. Some Judges believe that the commencement of business rescue proceedings does not affect the liability of sureties and others are of the view that the beginning of business rescue proceedings releases sureties from their obligations towards creditors unless business rescue plan or deed of suretyship provides otherwise. It is therefore recommended that our legislature introduces some new sections into the companies act. One Section should be similar to section 524(e) of the bankruptcy codes which expressly states that a discharge granted to the principal debtor does not affect the liability of sureties towards creditors. Another section should be similar to section 105(a), which provide courts with powers to make any order to realize the objectives of the companies act. This to avoid conflicting courts decisions on this issue.
Keywords: Bankruptcy; Creditors' rights; Insolvency; Liability of sureties; Reorganisation process; Suretyship

Les procédures collectives des établissements de crédits dans l'espace OHADA - Gueye, Ramata (Université Cheikh Anta Diop, 2018)

Entreprise en difficulté et statut coopératif - Michelin, Laura (Université de Reims Champagne-Ardenne, 2015)
La notion d'entreprise en difficulté est une notion particulièrement large recouvrant tout à la fois le domaine des procédures collectives mais également les mesures préventives. La coopérative, elle, correspond à une typologie de société dotée d'un statut spécifique où se côtoient des valeurs et des principes tout à fait atypiques (principe de double qualité, principe de démocratie, …). Lorsque les coopératives sont confrontées à des difficultés, elles sont soumises au droit des entreprises en difficulté dans son entière acception. Pour autant, leurs principes directeurs auront des incidences sur le déroulé de cette procédure que nous nous proposons d'analyser dans ces travaux. Nous évoquerons donc les divers principes coopératifs et leurs incidences lors des différentes étapes de la mise en place de procédure collective ou de procédure amiable. L'analyse de ces spécificités se fera par le biais d'une mise en confrontation de trois droits : le droit coopératif, le droit des sociétés et le droit des entreprises en difficulté. Il nous sera amené de constater que, bien que non formalisées par le législateur, les spécificités des coopératives en difficulté sont, dans la pratique, indéniables.
Keywords: Corporate law; Droit coopératif; Droit des entreprises en difficulté; Droit des sociétés; Entreprise en difficulté; Procédure amiable; Procédure collective